Vitamin B1 Deficiency Related to Excessive Soft Drink Consumption in Japan. Issue 5 (May 2018) - Okumura, Akihisa; Ida, Shinobu; Mori, Masaaki; Shimizu, Toshiaki
Abstract : ABSTRACT: The aim of this study was to clarify the picture of vitamin B1 deficiency (VB1D) caused by excessive soft drink consumption in Japan. A nationwide survey of children with soft drink-induced VB1D was conducted using a structured research form. Patient information was obtained from 2 sources: training hospitals for board-certified pediatricians and those identified by a database search. We obtained data from 33 children. Twenty-one children had a nonnurturing home environment. The median duration of excessive soft drink intake was 3.5 months and the daily intake was 1000 mL or more in 25 children. Infection was the most common reason for excessive soft drink consumption. Only 4 children had the classical triad of Wernicke encephalopathy. One child died, and 12 had neurological sequelae. A majority of children with soft drink-induced VB1D did not have a nurturing home environment. It is imperative to establish measures to prevent future cases of VB1D. Abstract : Supplemental Digital Content is available in the text